1997
DOI: 10.1038/bjc.1997.346
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding history, pregnancy experience and risk of breast cancer

Abstract: Summary Epidemiological evidence suggests that breastfeeding protects against breast cancer. Whether an effect of age at first breastfeeding is independent of an effect of age at first birth is unclear. We hypothesized that nausea and vomiting in pregnancy, which are associated with elevated serum oestradiol levels during pregnancy, may increase risk. Cases were 452 parous, premenopausal women, 40 years or younger, diagnosed with breast cancer in Los Angeles County from July 1983 to December 1988. Control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
4
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 34 publications
2
47
4
8
Order By: Relevance
“…Enger et al 21 found that lactation had a stronger protective effect in the first 5 years after a pregnancy. Our findings confirm this observation, although we also observed a protective effect associated with lactation in younger women who had given birth Ͼ 5 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Enger et al 21 found that lactation had a stronger protective effect in the first 5 years after a pregnancy. Our findings confirm this observation, although we also observed a protective effect associated with lactation in younger women who had given birth Ͼ 5 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…At least two previous studies have examined possible associations between nausea during pregnancy and subsequent risk of developing breast cancer. One (Troisi et al, 1998) found a decreased risk following one or more pregnancies with selfreported nausea, whereas the other (Enger et al, 1997) instead observed a slight risk increase after hospital care for hyperemesis. The reasons for the conflicting results are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being the second most common cause of mortality in women following the lung cancer, the breast cancer could have a good prognosis by correct management of the disease (McCullough et al, 2014). Several factors are involved in the development of breast cancer including advanced age, family history, radiation therapy in young age, history of pregnancy and breast-feeding and hormone therapy (Enger et al, 1997). Less than 1% of breast cancer cases arise before 25 years of age but after 30, the incidence increases significantly and also increases with advancing the age (Jemal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%